Efektivitas Metode Pembelajaran Al-Qur’an: Kajian Literatur terhadap Iqra, Tilawati, dan Ummi - Taufiqurrahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The method of Qur'anic instruction plays a central role in shaping students' religious literacy skills from an early age. This article aims to evaluate the effectiveness of three popular methods in Qur'an reading education: Iqra, Tilawati, and Ummi, by reviewing relevant literature. Each method offers distinct approaches and characteristics in developing students’ ability to read the Qur’an with proper tajwid and tartil. The review reveals that all three methods are effective within specific contexts: Tilawati excels in musicality and reading fluency, Iqra emphasizes speed and foundational literacy, and Ummi focuses on nurturing religious values and emotional engagement. This study suggests that selecting an appropriate method should align with the learners’ characteristics and the goals of Qur'anic instruction.